Genetic Evidence for Indo-Western Pacific Olive Ridley Sea Turtles in Mexican Waters - Rodolfo Martín-del-Campo; Christian D. Ortega-Ortiz; Alberto Abreu-Grobois; Luis M. Enríquez-Paredes; David Petatán-Ramírez; Alejandra García-Gasca; Sonia I. Quijano-Scheggia (Diversity, 2023)
The olive ridley sea turtle is predominantly an epipelagic species with no apparent migration corridors. Research in feeding areas in other sea turtle species has identified aggregations of individuals from diverse backgrounds; however, no specific feeding areas have been identified for the olive ridley. We used mtDNA control region sequencing to identify the haplotype composition of 85 olive ridley turtles (adult and immature turtles from both sexes) captured and released in Central Mexican Pacific waters. Amplified fragments of the control region (751 bp) revealed the presence of 17 haplotypes (h = 0.5877 ± 0.0622 and π = 0.001698 ± 0.001185), and 16 of them were phylogenetically grouped within the lineage of the Eastern Pacific, but the haplotype Lo37 showed close evolutionary relationships with the lineage of the East Coast of India. Lagrangian drifter data showed that West–East transport from the Indo-Pacific to the tropical Eastern Pacific might be possible through passive drift. These results highlight the importance of more genetic studies offshore and the role of the ocean currents in the migratory behavior of olive ridleys, as well as the need to establish multinational strategies for the conservation and management of the species in international waters.